Demographic Characteristics of Differentiated Thyroid Carcinoma Patients Treated with Radioiodine at INMAS, Suhrawardy - Initial Experience with first 35 Patients (Bangladesh Journal of Nuclear Medicine, 2025)
Background: Differentiated thyroid carcinoma (DTC) is among the most curable cancers and relatively uncommon malignancy. These patients are treated by radio-iodine ablation (RAIA). In 1940s, radio-iodine ablation (RAIA) treatment for differentiated thyroid carcinoma (DTC) patients were first introduced in the world and in our country, it was in 1980. For treatment and lifelong follow up of DTC patients, we record all the medical documents at the thyroid division of Institute of Nuclear Medicine & Allied Sciences (INMAS), Suhrawardy. Objectives: To evaluate the response of radioiodine treatment in DTC patients at INMAS, Suhrawardy and analyze the outcome of patients in a single institute. Patients and Methods: This is a retrospective study. A total of 35 patients with DTC received RAI ablation therapy from august 2024 to December 2024 at INMAS, Suhrawardy. Data were obtained from the medical records of 35 DTC patients who were treated until December 2024 and all relevant data were available. Demographical, histopathological, surgical, radioiodine ablation doses of 131I, serum biomarkers thyroglobulin (Tg), antithyroglobulin antibody (TgAb) and biochemical investigation data were analyzed systematically. Age, gender, tumor size, presence of local and distant metastases at presentation, extrathyroidal extension (ETE), disease recurrence, and cancer-specific survival were also evaluated. Risk stratifications for recurrence and staging were calculated for dosing of radioiodine. The single dose of radioiodine ranged from 30 mCi to 150 mCi was given according to the postsurgical risk assessment. Results: The median age of DTC patients was 36 years, with a range of 21-68 years (39.40± 12.16 years), with the majority of patients falling within the 31-40 age group. The ratio of female to male was 3.375:1. Papillary thyroid carcinoma (PTC) 25(71%), follicular variant of thyroid carcinoma (FVPTC) 8(23%) and follicular thyroid carcinoma (FTC) 02(6%) was diagnosed in our institute. Excellent response (ER) was observed by a single dose of radioiodine ablation in 35(100%). Conclusion: As a new institute we observed that, significant number of DTC patients was increased in day by day. ER was noted in 100% with a single dose of radioiodine still now.Bangladesh J. Nuclear Med. 27(2): 217-221, 2024